Peasant organization in coffee communities: La Sombra Chiconquiaco, Veracruz, Mexico - Hernández-Romero, Oliverio; Zaragoza Martínez, Elena; Estrada-Quiterio, Freddy A.; Álvarez González, Xochitl; Rivera Peña, Rubén; Morales Lormendez, Ignacio (Revista Mexicana de Ciencias Agrícolas, 2017)
This investigation notes explores the various forms of association and organization that peasants working on coffee have. We discuss the differences between association and organization and a case study is shown to identify these concepts. It starts from the conception of man as an eminently social being, and transiting towards the characteristics and the constitution of the collective subjects from the collective consciousness that is formed when interacting each individual within this social subject. The concepts of association and organization are open to discussion based on the basic premise that the association allows individuals to participate by making decisions that affect them in their daily lives. And in the case of the organization, the people who hold power organize the work of others, i.e., workers or employees, in order to achieve their own objectives and in the case of the association, the partners join their individual economic powers, to form a greater power and to use it in the attainment of its aims. By the above, a society must be understood as an association, while an organization must be understood as a company. Understood as an “instrument to establish purposes, to be constituted as a collective subject and to join forces or individual powers to form a greater power, sufficient to relate positively and successfully with other subjects on the road to the realization of the goals set by the peasants themselves.